Formation of chromatographically unique species of transfer ribonucleic acid during amino acid starvation of relaxed-control Escherichia coli. - Fournier, M J (1975)
Examination of the transfer ribonucleic acid (tRNA) produced by starving, relaxed-control (rel minus) strains of Escherichia coli for required amino acids revealed the occurrence of a number of chromatographically unique subspecies. Leucine starvation results in the formation of new isoacceptor species of leucine-, histidine-, arginine-, valine-, and phenylalanine-specific tRNA and quantitative changes in the column profiles of serine, glycine, and isoleucine tRNA. Evidence that the unique tRNA species are synthesized de novo during amino acid starvation comes from the findings that the major unique leucine isoacceptor species is not formed in stringent control cells or in rel minus cells starved for uracil or treated with rifampin. Furthermore, heat treatment of the unique leucine tRNA does not alter its chromatographic behavior, indicating that the species is not an aggregate or nuclease-damaged form of a normal isoacceptor tRNA. The methyl acceptor activities of tRNA from leucine-starved and nonstarved rel+ or rel minus cells were found to be essentially the same. This result and the finding that the chromatographic behavior of the unique leucine-specific tRNA was not altered after treatment with tRNA methylase suggests that gross methyl deficiency is probably not the biochemical basis for the occurrence of the unique species.